0851 Sleep Duration and Asthma Outcomes in Adolescents. (27th April 2018) - Meltzer, L J; Jump, S; Flewelling, K D; Sundstrom, D; White, M; Strand, M J
Abstract: Introduction: Asthma is the most common pediatric chronic illness, impacting approximately 10% of adolescents. There is a need to examine modifiable behaviors, such as sleep duration, which may reduce the morbidity of asthma (e.g., missed school days). Using an established sleep-manipulation protocol, this study examined the impact of sleep duration on objective and subjective measures of lung function. Methods: Fifty-four adolescents (68.5% female; 66.7% White; 25.9% Hispanic; mean age=14.7 years) completed a 3-week randomized, cross-over protocol. Following a week of sleep stabilization, adolescents were randomized to 5 nights of insufficient (short) sleep opportunity (6.5 hrs in bed) and healthy (long) sleep opportunity (9.5 hrs in bed). Wake time remained consistent across all three weeks. Participants completed daily peak expiratory flow rates (PEFR) within 30 minutes of waking and 12 hours later, weekly spirometry and exhaled nitric oxide (eNO), and the PROMIS Asthma Impact Scale. Results: For peak flow meter data, a significant overnight mean change in FEV1 was found for the short week (82 mL decrease, p =.004), but not the long week (24 mL decrease, p =.45). A significant overnight change was also found in PEFR for both the short and long weeks ( p =<.0001 and p =.0003 respectively), but was greater during the short week (mean drop of 20.3 vs. 14.7 L/min). No significant differences between study weeks were found for weekly spirometry or eNO. Self-reported asthma symptoms and asthma impact were worse during the short week vs. the long week ( p =.07). Conclusion: Objective and subjective changes in asthma were found during a week of deficient sleep, with worse lung function measured by daily peak flow and increased subjective asthma symptoms/asthma impact. However, no differences were found for spirometry or eNO performed in a clinical setting. Because objective lung function measures are effort dependent, sleep deprived adolescents may perform worse at home than when trained professionals are coaching them. That said, subjective asthma symptoms in combination with daily peak flow are often used to make treatment decisions; thus a better understanding of the relationship between sleep duration and asthma is needed. Support (If Any): NIH-R01HL119441.